Analisis Hukum pada Menerima Upah Mengajar Al-Qur'an Menurut Fiqh Hanafi dan Fiqh Asy-Syafi'i Studi Kasus Kecamatan Medan Deras Kabupaten Batu Bara - Ramadina, Wardah; Syam, Syafruddin; Ramadani, Ramadani (AHKAM, 2023)
Wages are a right that must be paid to workers as compensation for the work they have done. Islam provides guidelines that the payment of wages is made upon completion of a job. The aim of this research is to find out what the opinions of Hanafi fiqh and Ash-Shafi'i fiqh are regarding receiving wages for teaching the Koran and to find out which opinion is the most persistent between the opinions of Hanafi fiqh and the opinion of Ash-Shafi'i fiqh. The type of research used is normative sociological research using a descriptive and comparative approach and the raw material sources used in this research are primary and secondary material sources. The results of this research are that between Hanafi fiqh and Ash-Shafi'i fiqh there are differences of opinion regarding receiving wages for teaching the Koran. The Hanafi fiqh opinion does not allow receiving wages for teaching the Koran, while the Ash-Shafi'i fiqh opinion allows receiving wages for teaching the Koran.